Gender inequality and judicial discretion in Muslims divorce of Indonesia - Ramadhita Ramadhita; Mahrus Ali; Bachri Syabbul (Cogent Social Sciences)
Divorce of Muslims should be carried out in court, as opposed to the classical fiqh teachings still adhered to in some countries. In practice, this process is still gender biased and detrimental to women. Therefore, this doctrinal legal research uses historical and conceptual approaches to eliminate gender inequality in Muslim divorce procedures. This is a qualitative research with data collected from secondary sources in the form of laws and articles on the divorce of Muslims in various countries, especially in Indonesia. The findings indicate that there is gender inequality in the divorce procedural law in Indonesia. For instance, a wife loses the rights guaranteed by the law of a joint residence. Additionally, the wife cannot file for divorce at the place of domicile because it is considered disobedient to the husband. In many cases, the wife leaves the husband because of domestic violence. For this reason, judges’ discretion is needed as a form of the active role of the state in eliminating gender inequality in the divorce process, thereby protecting women’s rights.